A novel chemometrics method for Halal authentication of gelatin in food products - Nurfarhana Hassan; Tahir Ahmad; Norhidayu M. Zain; Azmirul Ashaari (Penerbit Universiti Kebangsaan Malaysia, 2020)
The issue of halal authenticity of food and pharmaceutical products has become a concern to Muslims due to fraud and unknown sources of ingredients. The most common non-halal ingredient found in some food products and also in capsule medicine is porcine gelatin. Other sources of gelatin are bovine and fish. Numerous methods have been developed to identify between bovine, porcine, and fish gelatins due to the concern on the halal authenticity issue. Fourier transform infrared (FTIR) spectroscopy is one of the established techniques in food adulteration analysis. However, further analysis using chemometrics method is required due to the large similarities of the gelatin spectra. This paper introduces a novel chemometrics method using Fuzzy Autocatalytic Set (FACS) to determine the FTIR spectra of bovine, porcine, and fish gelatins. The unique dominant regions for these gelatins were identified. The bovine, porcine, and fish gelatins possessed different dominant region when compared to each other. The FACS method offers simple and rigorously computational procedure to differentiate bovine, porcine, and fish gelatins for halal authentication purposes.